Implementasi E-Filing Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi - Miftha Rizkina; Nur Aliah; Sumardi Adiman (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to analyze the implementation of the level of utilization, and the impact of the use of E-Filing on the level of taxpayer compliance at the East Medan Pratama Tax Service Office. This study uses a qualitative approach with the analytical descriptive research method. Data collection techniques in this study consisted of literature studies, interviews, and also field research. The results of this study indicate that the implementation of the E-Filing system at KPP Pratama Medan Timur is in accordance with the provisions of tax administration and tax laws and regulations. The level of utilization of E-Filing has been effectively running well and has met the late target set by KPP Medan Timur and the implementation of E-Filing has not had a positive impact in terms of increasing taxpayer compliance, this can be seen from the decreased level of taxpayer compliance every year. This study shows that although the implementation and utilization measure of E-Filing system is considered decent, it turns out that E-Filing system has no effect on the measure of taxpayer compliance.